2011
DOI: 10.1038/nrclinonc.2011.106
|View full text |Cite
|
Sign up to set email alerts
|

Organ-sparing radiation therapy for head and neck cancer

Abstract: To improve locoregional tumor control and survival in patients with locally advanced head and neck cancer (HNC), therapy is intensified using altered fractionation radiation therapy or concomitant chemotherapy. However, intensification of therapy has been associated with increased acute and late toxic effects. The application of advanced radiation techniques, such as 3D conformal radiation therapy and intensity-modulated radiation therapy, is expected to improve the therapeutic index of radiation therapy for H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 122 publications
1
69
1
Order By: Relevance
“…Also, other recently published reviews e.g. , Cartmill (2012), Nutting (2012), Bhide (2012) and colleagues, concluded that although the evidence is small, a number of dosimetric constraints might be influential in minimizing the negative impact on swallowing, and potentially on nutritional outcomes [4,5,16,18] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, other recently published reviews e.g. , Cartmill (2012), Nutting (2012), Bhide (2012) and colleagues, concluded that although the evidence is small, a number of dosimetric constraints might be influential in minimizing the negative impact on swallowing, and potentially on nutritional outcomes [4,5,16,18] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that IMRT in head and neck cancer treatment reduces overall adverse effects such as xerostomia and dysphagia, and thus improves quality of life, even when chemotherapy is added to IMRT (chemo-IMRT) [1][2][3][4][5]. It appears possible to limit the dose to the musculature involved in swallowing and mastication without compromising radiation to the tumor site(s) [2,3,5,6]. In many institutes, therefore, IMRT has become the standard of care in head and neck cancer.…”
Section: Introductionmentioning
confidence: 99%
“…For the clinical target volume (CTV) a margin of 5 -10 mm was added to GTV and corrected for anatomical boundaries. The elective nodal volumes were defi ned per national guidelines [1]. A uniform margin of 4 mm was added to CTV to correct for systematic and random patient setup uncertainties resulting in the planning target volume (PTV).…”
Section: Radiation Treatment Planningmentioning
confidence: 99%
“…Patient's commonly suffer from xerostomia, dysphagia, and hearing loss, whilst osteoradionecrosis of the mandible, radiation-induced nerve palsy, and cerebral radiation necrosis are much less common [40]. Salvage surgery for recurrent disease is also made difficult in a previously irradiated region, secondary to significant fibrosis and loss of normal tissue planes.…”
Section: Radiation Therapymentioning
confidence: 99%
“…Post-operative radiotherapy is often commenced six weeks postoperatively, allowing for adequate tissue healing, and delivers 60-66 Gy [30]. The advent of intensity-modulated radiation therapy, allows radiation oncologists to deliver radiation in 3 dimensions using CT-planning thus targeting specific sites and avoiding structures at risk such as the optic nerves, brain stem, spinal cord, salivary glands, inner ear, swallowing structures and mandible [40].…”
Section: Radiation Therapymentioning
confidence: 99%